Certification of Human Resources, Skills, and Welfare as Performance Determinants in the Operational Area of PT. Patra Niaga DOK Dumai Terminal - Ridho, Syarifur; Saturut, Irfan Toro Manullang; Maulana, Rio; Waruru, Dealis (Universitas Hang Tuah, 2025)
This study aims to analyze the effect of Human Resources (HR) certification, technical skills, and employee welfare on operational performance at the PT Patra Niaga DOK Dumai terminal in 2024. Of the 200 employees surveyed, 78% have relevant certifications in operational management and occupational safety. Certified workers show a 55% higher productivity level (28 containers/hour) compared to those who are not certified (18 containers/hour). Technical and managerial skills obtained through continuous training are able to optimize the loading and unloading process and terminal services. Meanwhile, employee welfare—including safety assurance, fair compensation, and a supportive work environment—increases motivation, loyalty, and reduces work incidents by up to 33%. Survey data shows that 85% of respondents rate their level of welfare as good, especially in terms of safety and compensation. The research method uses a quantitative approach with data collection techniques through structured surveys, in-depth interviews, and internal company documentation. The results of this study confirm that the combination of formal certification, skills development, and welfare programs contribute significantly to achieving superior operational performance. This finding strengthens previous literature that emphasizes the importance of workforce support systems in improving Port productivity.